Open-Coil Retraction Spring - Pavankumar Janardan Vibhute (Hindawi Limited, 2011)
Sliding mechanic has become a popular method for space closure with developments in preadjusted edgewise appliance. Furthermore, various space closing auxiliaries have been developed and evaluated extensively for their clinical efficiency. Their effectiveness enhanced with optimum force magnitude and low-load deflection rate (LDR)/force decay. With the advent of NiTi springs in orthodontics, LDRs have been markedly reduced. For use of NiTi, clinician has to depend upon prefabricated closed coil springs. "Open Coil Retraction Spring (OCRS)" is developed utilizing NiTi open-coil spring for orthodontic space closure. This paper describes fabrication and clinical application of OCRS which have number of advantages. It sustains low LDR with optimum force magnitude. Its design is adjustable for desired length and force level. It is fail-safe for both activation and deactivation (i.e., it cannot be over activated, and decompression limit of open coil is also controlled by the operator, resp.). A possibility to offset the OCRS away from mucosa helps to reduce its soft-tissue impingement.